EXPLORING THE IMPACT OF STRESS MANAGEMENT ON SERVICE DELIVERY IN RIVERS STATE’S FAST-FOOD INDUSTRY - Chukwuemeka , John Ebube (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In the fast-food industry, one of the most challenging issues that the managers have to face is related to the stress of work. This is one factor that casts its effect on the performance of employees no matter the level they work (Ross, 2005). This study examined the impact of stress management on the quality of services in fast-food companies in Rivers State. The study was a descriptive survey for a target population that comprised of five (5) branches of five (5) fast-food companies in Port Harcourt, Rivers State. The simple random sampling design was employed in the organization and in order to ensure that the population was given equal chances of being selected for the study and the sources of data for the study were from both primary and secondary sources. Data was analyzed using frequencies, percentages, mean and correlation coefficient was used to test the hypothesis. The findings of this study revealed that there is a significant relationship between flextime work and service reliability of fast-food companies in Rivers State. Also, there is a significant relationship between flextime work and service tangibility of fast-food companies in Rivers State. Further findings revealed that, there is a significant relationship between flextime work and service empathy of fast-food companies in Rivers State. Based on the findings from the research, it was concluded that Flexibility in work would benefit the organization through reliable, tangible and empathy in service delivery. Also, the workers can become more enthusiastic to balance the need of the work and their personal life. It was recommended that organizations and servicing companies should engage in flexible work arrangement for their staff since offering flexible working to employees can boost staff morale and improve their physical and mental wellbeing.